The Phenomenon of Toe Walking in Children, Disease or Habit: A Case Report - Chesa Yenni Mahdaniar Sjarfi (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: Some children experience abnormalities in the way they walk, such as toe walking in the form of "bilateral toeing out" or "bilateral tip toe." Bilateral toe walking, also known as “bilateral toeing out,” is a condition in which both of a child's feet tend to move outwards when they walk. On the other hand, “bilateral tip toe” is when a child walks by standing on the tips of the toes without touching heels to the floor. This study aimed to present cases of the toe walking phenomenon in children. Case presentation: A child checks for complaints on both legs and looks at calcium and vitamin D levels. The patient came with toe walking after the age of 2 years and complained of frequent pain and soreness in both legs for the last 2 weeks. The calcium level in the blood was 5.8 mg/dL, and the vitamin D level was 10 ng/ml. At the request of the patient's parents, X-rays of both extremities were carried out, and the results were within normal limits with no masses or fractures. The patient was diagnosed with bilateral toeing out and bilateral tip toe. The treatment provided by medical rehabilitation specialist doctors to patients is in the form of medical and non-medical therapy. Conclusion: The patient was diagnosed with bilateral toeing out and bilateral tip toe.